Ambiente virtual de aprendizagem: uma imersão no SESC SP Serviço Social do Comércio de São Paulo - Oliveira, Werley Carlos de (2015)
The growth of education distance mode and as a consequence, the use of virtual learning environments (VLE) indicate a paradigm shift in teaching and learning. However, despite the potential exercised by this format for dissemination of knowledge in the corporate media, strategies aimed at the transition from the classroom to the distance are not yet fully understood. We are in the Internet age, but the benefits of this tool for teaching methods need better understanding, which leads to an under-utilization of interactive possibilities in support of teaching and learning. In this research we intend to seek to elucidate the contribution that technology can bring to the training and development activities of the SESC SP employees. To do so, it sets up an analytical and reflective look from scholars on education and culture, corporate education, human resources, e-learning and results in educational activities. We use the theory of complexity of authors Edgar Morin, Humberto Maturana and Francisco Varela in order to analyze a course deployed in a virtual environment of the SESC SP learning. For this, first, we studied the adult learning process correlating concepts of Piaget and Vygotsky pedagogy from the concept of "andragogy" Malcolm Knowles, that can be applied to the education of the distance mode in enterprise environments; to eventually exploit the variety of tools available on that learning environment. This research allowed to observe, analyze and present the contributions resulting from the use of these tools, concepts and format of teaching and learning for adults at SESC SP